Protocol for the efficacy and safety of fecal microbiota transplantation in children with autism spectrum disorder: a prospective single-center, single-arm interventional study - Lin, Baixian; Zhu, Zhongsheng; Yang, Xiao; Li, Ziyuan; Zhou, Haokui; Luo, Mingjing; Guan, Jiaojie; Zou, Yigui; Chen, Hu; Zhuang, Zeling; Meng, Shiyun; Li, Wenwen; et al. (Frontiers in Pediatrics, 2025)
BackgroundAutism spectrum disorder (ASD) is a neurodevelopmental condition affecting 0.7% of children globally, with 90% experiencing comorbid gastrointestinal (GI) symptoms. Fecal microbiota transplantation (FMT) may modulate ASD symptoms via the microbiota-gut-brain axis (MGBA).MethodsThis open-label single-arm trial enrolls 30 children (2–12 years) with moderate-to-severe ASD, defined as a Childhood Autism Rating Scale (CARS) score of ≥36. Participants receive 3 nasojejunal FMTs (5 mL/kg) over 5 days. The primary outcomes are GI symptom improvement, assessed using the Gastrointestinal Symptom Rating Scale (GSRS), and ASD severity, assessed using the CARS. Secondary outcomes include social responsiveness (Social Responsiveness Scale, SRS), aberrant behaviors (Aberrant Behavior Checklist, ABC), and gut microbiota changes assessed by metagenomic next-generation sequencing (mNGS).Ethics and disseminationEthical approval obtained from Shenzhen Children's Hospital Ethics Committee. Results will be disseminated via peer-reviewed publications and conference presentations.Clinical Trial Registration: https://www.chictr.org.cn/showproj.html?proj=229136, identifier ChiCTR2400083998. Registered on 2024-05-08. Registered title: “Efficacy and safety of fecal microbiota transplantation in treatment of autism spectrum disorder: a prospective single-center intervention study”.